Auditory and visual reaction time and peripheral field of vision in helmet users - Adhilakshmi, Abbu Pillai; Karthiga, Uday Kumar Priyadarshini; John, Nitin Ashok (Journal of Bangladesh Society of Physiologist, 2016)
Background: The incidence of fatal accidents are more in two wheeler drivers compared to four wheeler drivers. Head injury is of serious concern when recovery and prognosis of the patients are warranted, helmets are being used for safety purposes by moped, scooters and motorcycle drivers. Although, helmets are designed with cushioning effect to prevent head injuries but there are evidences of increase risk of neck injuries and reduced peripheral vision and hearing in helmet users. A complete full coverage helmets provide about less than 3 percent restrictions in horizontal peripheral visual field compared to rider without helmet. The standard company patented ergonomically designed helmets which does not affect the peripheral vision neither auditory reaction time. Objective: This pilot study aimed to evaluate the peripheral field of vision and auditory and visual reaction time in a hypertensive, diabetic and healthy male and female in order to have a better insight of protective characteristics of helmet in health and disease. Method: This pilot study carried out on age matched male of one healthy, one hypertensive and one diabetic and female subject of one healthy, one hypertensive and one diabetics. The field of vision was assessed by Listers perimeter whereas auditory and visual reaction time was recorded with response analyser. Result : Gender difference was not noted in peripheral field of vision but mild difference was found in auditory reaction time for high frequency and visual reaction time for both red and green colour in healthy control. But lateral and downward peripheral visual field was found reduced whereas auditory and visual reaction time was found increased in both hypertensive and diabetic subject in both sexes. Conclusion: Peripheral vision, auditory reaction time and visual reaction time in hypertensive and diabetics may lead to vulnerable accident. Helmet use has proven to reduce extent of injury in motorcyclist and other two wheeler drivers. Bangladesh Soc Physiol. 2016, December; 11(2): 43-46